The written vocabulary in English of the grades V and VI pupils of Balara Elementary School as determined by their formal themes - Villamor, Esperanza P. 1940- (s.n.], 1969)
The study determined the vocabulary achievement in English of Grades V and VI pupils of Balara Elementary School as shown by their formal themes during the school year 1967-1968. It is primarily concerned with the written vocabulary of the intermediate pupils. As a whole, it pointed out that the development of a wide stock of vocabulary words must be one of the aims of an effective language arts program in the elementary school and that children should be exposed to varied and meaningful experiences from which they can acquire new words.